No laboratório da nação: poder camarário e vereança nos anos iniciais da formação do Estado Nacional Brasileiro em fins do primeiro Reinado e nas Regências, Mariana, 1828-1836 - Kelly Eleuterio Machado Oliveira (2013)
On October 1, 1828, the Imperial Majesty ordered the execution of the Letter of law by which the General Legislative Assembly determined the new Municipal Organization. Based on this law, the municipalities could no longer perform political functions, but only administrative ones. Hence, the Chamber lost its autonomy becoming subordinated to the General Council of the Province. From these considerations, the objective of this dissertation is to discuss how the City Council of Mariana worked and reorganized itself assuming that the institution had a strong heritage component, despite the changes due to the construction of the National State. It should also be considered to what extent the law of the 1828 Municipal Organization determined the actions of the City Council of Mariana. In a second moment, we will present the socioeconomic profile of the men of councillorship and their acting in the Laboratory of the Nation. Finally, we will focus our attention on the course of one of these men: Antonio José Ribeiro Bhering.